Tuning Intramolecular Stacking of Rigid Heteroaromatic Compounds for High‐Efficiency Deep‐Blue Through‐Space Charge‐Transfer Emission - Zhao, Zhennan; Zeng, Cheng; Peng, Xiaomei; Liu, Yuchao; Zhao, Haisong; Hua, Lei; Su, Shi‐Jian; Yan, Shouke; Ren, Zhongjie (Angewandte Chemie International Edition, 2022)
A series of ultrapure‐blue thermally activated delayed fluorescence (TADF) emitters featuring through‐space charge transfer (TSCT) have been constructed by close stacking between the donor and acceptor moieties in rigid heteroaromatic compounds. The obviously accelerated radiative transition of singlet excitons, the diminished vibrionic relaxation of ground and excited states, and the consequent reduced Stokes shift and the narrow emission are evident. The corresponding organic light‐emitting diodes (OLEDs) based on AC‐BO realize the best performance among all deep‐blue TSCT‐TADF emitters, with an external quantum efficiency (EQEmax) of 19.3 %. Furthermore, the OLEDs based on QAC‐BO display an EQEmax of 15.8 %, and achieve the first high‐efficiency ultrapure‐blue TSCT‐TADF material with an excellent Commission Internationale de L'Eclairage coordinate (CIE) of (0.145, 0.076) which perfectly matches the ultrapure‐blue CIE requirements (0.14, 0.08) defined by the National Television System Committee. Ultrapure‐blue through‐space charge‐transfer (TSCT) emitters have been constructed by the close intramolecular stacking of rigid heteroaromatic compounds. The corresponding organic light‐emitting diodes show the best performances among all currently reported deep‐blue TSCT thermally activated delayed fluorescence emitters and a sequentially hypochromic‐shift emission with CIEy coordinates ranging from 0.122 to 0.034.